2014
DOI: 10.3892/mmr.2014.2586
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of suilysin contributes to invasive infection of the Streptococcus suis strain 05ZYH33

Abstract: Streptococcus suis serotype 2 (SS2) is widely recognized in the veterinary world as the cause of rapidly progressive and fatal sepsis in infant pigs, manifested with meningitis, polyarthritis and pneumonia. It has evolved into a highly infectious strain, and caused two large-scale outbreaks of human epidemic in China, characterized bytypical toxic-shock syndrome and invasive infection. However, the molecular basis of virulence of this emerging zoonotic pathogen is still largely unknown. The present study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Moreover, ST-7 strains were more toxic to human peripheral blood mononuclear cells (PBMCs) than ST-1 strains (mainly referring to the European virulent strains)26. In particular, we have previously shown that the ST-7 strains produced more SLY than the non-epidemic strains, contributing to invasive infection27. Therefore, SLY may be a potential therapeutic target for preventing S. suis -mediated platelet activation, thrombocytopenia, liver failure and purpura gangrenosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ST-7 strains were more toxic to human peripheral blood mononuclear cells (PBMCs) than ST-1 strains (mainly referring to the European virulent strains)26. In particular, we have previously shown that the ST-7 strains produced more SLY than the non-epidemic strains, contributing to invasive infection27. Therefore, SLY may be a potential therapeutic target for preventing S. suis -mediated platelet activation, thrombocytopenia, liver failure and purpura gangrenosa.…”
Section: Discussionmentioning
confidence: 99%
“…The isogenic sly mutant Δsly was constructed in our previous study27. The Canadian avirulent strain 1330, which does not express SLY, was donated by Prof Marcelo Gottschalk (Université de Montréal).…”
Section: Methodsmentioning
confidence: 99%
“…SLY was shown to contribute to the development of bacterial meningitis and the increased mortality in mouse infection models (9). S. suis with an increased SLY production caused higher mortality in intraperitoneally infected mice than a nonvirulent strain, indicating that an increase in SLY production was associated with an enhanced S. suis virulence (10). Although the role of SLY in its contribution to human SS2 infections is not fully understood, SLY-positive strains have been reported to result in more severe symptoms than SLY-negative strains (11,12).…”
mentioning
confidence: 99%
“…However, the fact that many virulent serotype 2 strains (mainly from North America) as well as virulent strains belonging to other serotypes are not able to produce the suilysin, seems to indicate that this toxin does not play a critical role in virulence . Although it has been recently reported that increased suilysin production in virulent S. suis facilitates survival in mouse bloodstream after intraperitoneal infection , a previous work has shown that mutants lacking the suilysin are as virulent as the wild‐type strain after an aerosol infection in pigs . Confusing observations about the role of the suilysin as a virulence factor in both the early infection and meningitis caused by S. suis are due to the use of different animals models.…”
Section: How Does Streptococcus Suis Establish In Mucosa and Breakdowmentioning
confidence: 99%